TRADISI ZIARAH KUBUR: MOTIF DAN AKTIVITAS PENZIARAH DI MAKAM YANG DIKERAMATKAN - Jamal Mirdad; Helmina Helmina; Iril Admizal (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This article examines the activities and motives of pilgrims at the Grave Pilgrimage Tradition ceremony at the Mausoleum of Puyang Muaro Danau, Mande Rubiah and Sheikh Burhanuddin. The tradition of visiting the grave is a tradition that has existed for a long time, even indications that this tradition existed before the arrival of Islam. Although eras and times have changed, the tradition of visiting the graves has not been eroded by the times, the interest and intention of pilgrims to visit the existing tombs continues and is even more crowded. The method used in this research is a field research method with a qualitative-descriptive approach, the data collection tools are participatory observation, interviews and document studies. With the finding that the tradition of visiting the graves, both the activities and the motives of the pilgrims to several tombs were found to be different.